Test-retest reproducibility of binding parameters in humans with (11)C-LY2795050, an antagonist PET radiotracer for the kappa opioid receptor - Naganawa, Mika (J Nucl Med, 2015)
(11)C-LY2795050 is a new antagonist PET radioligand for the kappa opioid receptor (KOR). In this study, we assessed the reproducibility of the binding parameters of (11)C-LY2795050 in healthy human subjects. METHODS: Sixteen healthy subjects (11 men, 5 women) underwent two separate 90-min PET scans with arterial input function and plasma free fraction measurements. The two-tissue compartment model and multilinear analysis-1 were applied to calculate five outcome measures in 14 brain regions: distribution volume (V(T)), distribution volume normalized by plasma free fraction (V(T)/f(P)), and three binding potentials (BP(ND), BP(P), BP(F)). Since KOR is distributed ubiquitously throughout the brain, there are no suitable reference regions. We used a fixed fraction of individual cerebellum V(T) value as the non-displaceable distribution volume V(ND) (= V(T CER)/1.17). The relative and absolute test-retest variability and intra-class correlation coefficient were evaluated for the outcome measures of (11)C-LY2795050. RESULTS: The test-retest variability of (11)C-LY2795050 for V(T) was ≤ 10% in all regions, and 12% in the amygdala. For binding potentials (BP(ND) and BP(P)), the test-retest variability was good in regions of moderate and high KOR density (BP(ND) > 0.4) and poor in regions of low density. Correction by f(P) (V(T)/f(P) or BP(F)) did not improve the test-retest performance. CONCLUSION: Our results suggest that quantification of (11)C-LY2795050 imaging is reproducible and reliable in the regions with moderate and high KOR density. Therefore we conclude that this first antagonist radiotracer is highly useful for PET studies of KOR.